PL.39 Incidence and Risk Factors for Severe PPH: A Prospective South East Cohort Study (STOP). (26th April 2013) - Briley, A; Tydeman, G; Seed, PT; Ballard, H; Sandall, J; Tribe, RM; Bewley, S
Abstract : Introduction: Postpartum haemorrhage(PPH) is common, rising and treatable (1). Most women are not compromised until estimated blood loss (EBL) exceeds 1000 ml (2). Major PPH remains a cause of maternal death (3) but definitions vary, making comparisons difficult. The Scottish population-based annual audit reported 0.55% incidence of PPH ≥ 2500 ml, the highest since inception (4). Aims: To ascertain the incidences of severe PPH defined as EBL ≥1000 ml, ≥1500 ml and ≥2500 ml in a prospective cohort from South East England. To determine risk factors associated with EBL at, and progressing from, these levels. Methods: Routine data were imported from 10, 213 women delivering in two units 2008–9. All cases with imported EBL ≥1000 ml and/or identified via blood transfusion services were reviewed. Weighted sampling and chronological stepwise regression analysis were performed. Incidence was compared historically (same geographical population 1997–8) and contemporaneously (Scottish Audit 2009). Results: Incidenc es of PPH ≥1000 ml, ≥1500 ml and ≥2500 ml were 10.1% (95%CI 4.8–6.0), 4.7% (95%CI 3.3–6.1) and 0.8% (95%CI 0.6–1.0) respectively. Historical rate of PPH ≥ 1500 ml = 1.12% (95%CI 0.92–1.38). Contemporaneous PPH ≥ 2500 ml was 0.55% (95%CI 0.5 to 0.6). Risk factors for severe PPH included BMI, generally unwell without diagnosis, anterior placenta praevia, chorioamnionitis, no labour, physiological 3rd stage of labour and interval to suturing. Previous, elective and emergency caesarean section were protective. Conclusions: Severe PPH rates are rising rapidly. These demonstrated are comparable with contemporaneous UK data. Risk factors for PPH and severe PPH differ. The underlying causes originate pre-pregnancy, through pre-exisiting health status and previous obstetric history, some are associated with quality of care. References: Knight M, Knight M, Callaghan WM et al, Trends in postpartum haemorrhage in high resource countries: a review and recommendations from the International Postpartum Hemorrhage Collaborative Group. BMC Pregnancy & Childbirth 2009; 9. Brace V, Penney G, Hall M. Quantifying severe maternal morbidity: a Scottish population study. BJOG 2004: 111(5):481–4. CMACE Saving mothers' Lives. BJOG 2011;118:1–203. Scotland Health Improvement. Scottish Confidential Audit of Severe Maternal Morbidity 7 th Annual Report 2011.